Представление L-почти периодических функций как непрерывные функции на топологической группе - Димитрова-Бурлаенко, Светлана Димова (НТУ "ХПИ", 2010)
В роботі розглянуто абстрактні функції, задані на групі зі значеннями в просторі Фреше. Введено визначення абстрактної L-майже періодичної функції, котра не обов’язково є неперервною. Сформульоване узагальнення теореми А. Вейля для таких функцій. Доведено, що будь яка L-майже періодична функція неперервна на групі у спеціальній топології, та що будь яка функція, котра неперервна у цій топології, є такою. Така спеціальна топологія існує для нескінченної множини указаних функцій.

The abstract (vector-valued) functions defined over a group with values in Freshet space were considered. A definition of vector-valued L-almost periodic function, that are not obligatory continuous has been introduced. Generalization of theorem A. Weyl for L-almost periodic functions with rang in a Freshet space is formulated. It is proven that any L-almost periodic function is continuous over the group in special topology and any function which is continuous in this special topology is L-almost periodic function. This special topology exists for infinite set of L-almost periodic functions.
Keywords: теоремы Вейля; функции Фреше; топологии; периодические функции